Spore 195: Smart farming - Transforming Agriculture with Artificial Intelligence - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Transforming Agriculture with Artificial Intelligence. At a time where the world needs to produce more with fewer resources, artificial intelligence (AI) could help to transform agriculture worldwide.